PEMBANGUNAN BERKELANJUTAN: PENGELOLAAN SUMBER DAYA ALAM BERBASIS PEMBANGUNAN SOSIAL DAN EKONOMI INDONESIA - Niza Utami; Rizky Febrian Saragih; Muli Daulay; M. Daffa Maulana; Purnama Ramadani (Journal of Management and Social Sciences, 2023)
This study aims to look at natural resource management based on Indonesia's social and economic development. The method used is a qualitative research method. The results show that formally it is clear that the development carried out in Indonesia must be in the form of Sustainable and Environmentally Friendly Development but it is still only in the form of das solen and through legal instruments it is hoped that this can be realized at the das sein level. However, this success still depends on many factors, apart from those that are juridical in nature, as well as political and cultural ones, including the condition of the human resources who are implementing them. The main principle in sustainable development is maintaining the quality of life for all humans in the present and in the future in a sustainable manner. Sustainable development is carried out with the principles of economic welfare, social justice and environmental preservation.